Solid electrolyte
A solid electrolyte with controlled molar ratios of Li, P, S, O, and X in an Argyrodite-type crystal structure addresses the degradation and conductivity issues of existing sulfide electrolytes, achieving high ionic conductivity and reduced hydrogen sulfide generation.
Patent Information
- Application Number
- JP2024192815
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-16
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-09-18
AI Technical Summary
Existing sulfide solid electrolytes are degraded by water in the air and suffer from insufficient hydrogen sulfide generation, which affects their ionic conductivity.
A solid electrolyte composition with a specific molar ratio of lithium (Li), phosphorus (P), sulfur (S), oxygen (O), and halogen (X) is formulated to suppress hydrogen sulfide generation and enhance ionic conductivity, utilizing an Argyrodite-type crystal structure with controlled molar ratios (4.8 ≦ Li/P ≦ 5.3, 3.8 ≦ S/P ≦ 4.4, 0 < O/P ≦ 0.8, 1.0 < X/P ≦ 2.0) and a manufacturing process involving mixing and heating.
The solution effectively suppresses hydrogen sulfide generation while maintaining high ionic conductivity, achieving a solid electrolyte with improved performance.
Smart Images

Figure 2025013456000005 
Figure 2025013456000006 
Figure 2025013456000007
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte and a method for manufacturing the same.
Background Art
[0002] Sulfide solid electrolytes are known to deteriorate due to moisture in the air. On the other hand, for example, Patent Document 1 discloses Li 7-a PS 6-a Ha a (where Ha represents a halogen; a satisfies 0.2 < a ≤ 1.8) and Li3PS4, and in the X-ray diffraction pattern obtained by measurement using the X-ray diffraction method (XRD), the ratio of the peak intensity appearing at a diffraction angle 2θ = 26.0 to 28.8° derived from Li3PS4 to the peak intensity appearing at a diffraction angle 2θ = 24.9 to 26.3° derived from the Argyrodite-type crystal structure is 0.04 to 0.3. A solid electrolyte is disclosed. Patent Document 2 discloses a sulfide solid electrolyte in which an alkaline compound is mixed in the solid electrolyte, and the ratio of the molar amount of the alkali metal contained in the alkaline compound to the molar amount of Li contained in the solid electrolyte is 1 / 1000 or more and 1 / 25 or less.
[0003] Further, Patent Documents 3 and 4 disclose sulfide-based solid electrolyte particles containing lithium, phosphorus, sulfur, and a halogen and having a cubic Argyrodite-type crystal structure, and sulfide-based solid electrolytes for lithium secondary batteries whose surfaces are coated with a compound having a non-Argyrodite-type crystal structure containing lithium, phosphorus, and sulfur.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
[0005] The solid electrolytes of Patent Documents 1 to 4 are insufficient in both suppressing hydrogen sulfide generation and providing good ion conductivity, and further improvements are required. An object of the present invention is to provide a solid electrolyte that suppresses the generation of hydrogen sulfide and has high ionic conductivity, and a method for producing the same. [Means for solving the problem]
[0006] According to one embodiment of the present invention, there is provided a method for producing a solid electrolyte having an argyrodite-type crystal structure, comprising: a mixing step of mixing raw materials so that lithium (Li), phosphorus (P), sulfur (S), oxygen (O), and halogen (X) satisfy the following formulas (11) to (14); and a heating step of heating the mixture obtained by the mixing step. 4.8≦Li / P≦5.3 (11) 3.8≦S / P≦4.4 (12) 0 <O / P≦0.8 ···(13) 1.0 <X / P≦2.0 ···(14) (Equation (11) is the molar ratio of Li to P, equation (12) is the molar ratio of S to P, equation (13) is the molar ratio of O to P, and equation (14) is the molar ratio of halogen (X) to P.)
[0007] According to one embodiment of the present invention, there is provided a solid electrolyte having an argyrodite-type crystal structure containing lithium (Li), phosphorus (P), sulfur (S), oxygen (O) and a halogen (X), in which the proportion of Li3PO4 crystal structures in all crystals in the solid electrolyte is 0.1 mass % or more and 3.0 mass % or less, and which satisfies the following formulas (21) to (23): 4.8≦Li / P≦5.3 (21) 3.8≦S / P≦4.4 (22) 1.0 <X / P≦2.0 ···(23) (Equation (21) is the molar ratio of Li to P, equation (22) is the molar ratio of S to P, and equation (23) is the molar ratio of halogen (X) to P.) Effect of the Invention
[0008] According to the present invention, it is possible to provide a solid electrolyte that suppresses the generation of hydrogen sulfide and has high ionic conductivity, and a method for producing the same. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic diagram of a test device for measuring the amount of hydrogen sulfide generated. [Diagram 2] 1 is an X-ray diffraction (XRD) pattern of the solid electrolyte obtained in Example 1. [Diagram 3] 1 is an XRD pattern of the solid electrolyte obtained in Example 2. [Figure 4] 1 is an XRD pattern of the solid electrolyte obtained in Example 3. [Diagram 5] 1 is an XRD pattern of the solid electrolyte obtained in Example 4. [Figure 6] 1 is an XRD pattern of the solid electrolyte obtained in Comparative Example 1. [Figure 7] 1 is an XRD pattern of the solid electrolyte obtained in Comparative Example 2. [Figure 8] 1 is an XRD pattern of the solid electrolyte obtained in Comparative Example 3. [Figure 9] 1 is an XRD pattern of the solid electrolyte obtained in Comparative Example 4. [Figure 10] 1 is an XRD pattern of the solid electrolyte obtained in Comparative Example 5. [Figure 11] 1 is an XRD pattern of the solid electrolyte obtained in Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [First embodiment] A method for producing a solid electrolyte according to one embodiment of the present invention includes the following mixing step and heating step, and produces a solid electrolyte having an argyrodite-type crystal structure. Mixing step: a step of mixing raw materials so that lithium (Li), phosphorus (P), sulfur (S), oxygen (O) and halogen (X) satisfy the following formulas (11) to (14): 4.8≦Li / P≦5.3 (11) 3.8≦S / P≦4.4 (12) 0 <O / P≦0.8 ···(13) 1.0 <X / P≦2.0 ···(14) (Equation (11) is the molar ratio of Li to P, equation (12) is the molar ratio of S to P, equation (13) is the molar ratio of O to P, and equation (14) is the molar ratio of halogen (X) to P.) Heating step: a step of heating the mixture obtained by the mixing step.
[0011] In this embodiment, by adjusting the composition of the starting materials to satisfy the formulas (11) to (14), the sulfur ions (S 2- ) decreases, and the amount of halogen ions (Cl - , Br - It is presumed that an argyrodite-type crystal structure in which the amount of argyrodite is increased is formed. The argyrodite crystal structure is PS4 3- The structure is the main unit structure of the framework, and the surrounding sites are S surrounded by Li. 2- and optionally halide ions. The general argyrodite crystal structure is a crystal structure represented by the space group F-43M. This crystal structure is crystallographically known as PS4 3- There are 4a sites and 4d sites on the periphery of the structure, and elements with a large ionic radius tend to occupy the 4a sites, while elements with a small ionic radius tend to occupy the 4d sites.
[0012] The unit cell of the argyrodite-type crystal structure has a total of eight 4a sites and 4d sites. The inventors of the present application have found that S occupying the sites in the argyrodite-type crystal structure 2- It is assumed that this is the cause of hydrogen sulfide generation, and the S 2- It has been found that the generation of hydrogen sulfide can be reduced by relatively lowering the content of On the other hand, it was confirmed that if the amount of S in the starting materials is simply reduced, some elements will not form the argyrodite-type crystal structure during the heating process, but will instead form crystal phases other than the argyrodite-type crystal, such as β-Li3PS4, resulting in a significant decrease in ionic conductivity. As a result of intensive research by the present inventors to solve the problem, it was surprisingly found that by using the compositions of the above formulas (11) to (14) and by including O in the starting materials, the formation of crystal phases other than argyrodite-type crystals such as β-Li3PS4 during the heating step is suppressed, and the S in the crystals is suppressed. 2- The inventors have found that it is possible to increase the amount of the argyrodite-type crystal structure in which the amount of hydrogen sulfide is reduced, thereby obtaining a solid electrolyte having high ionic conductivity while sufficiently suppressing the generation of hydrogen sulfide.
[0013] It is preferable that the above formulas (11) to (14) in the mixing step satisfy the following formulas. 4.85≦Li / P≦5.25 3.9≦S / P≦4.3 0.01≦O / P≦0.7 1.2≦X / P≦1.9 More preferably, the above formulas (11) to (14) in the mixing step satisfy the following formula: 4.9≦Li / P≦5.2 4.0≦S / P≦4.2 0.05≦O / P≦0.6 1.4≦X / P≦1.8
[0014] The raw materials used in this embodiment are a combination of two or more compounds and / or simple substances so that the solid electrolyte to be produced contains the essential elements at a predetermined molar ratio. Specifically, a combination of two or more compounds and simple substances containing Li, P, S, O, and halogen (X) as a whole is used.
[0015] Examples of the raw material containing lithium include lithium compounds such as lithium sulfide (Li2S), lithium oxide (Li2O), lithium carbonate (Li2CO3), and lithium hydroxide (LiOH), as well as elemental lithium metal, etc. Among these, lithium compounds are preferred from the viewpoint of ease of handling the raw material and ease of reaction, and Li2S is more preferred.
[0016] Examples of raw materials containing phosphorus include phosphorus sulfides such as diphosphorus trisulfide (P2S3) and diphosphorus pentasulfide (P2S5), phosphorus compounds such as sodium phosphate (Na3PO4), and elemental phosphorus. Among these, phosphorus sulfide is preferred from the viewpoint of ease of handling and ease of reaction, and diphosphorus pentasulfide (P2S5) is more preferred. Phosphorus compounds such as diphosphorus pentasulfide (P2S5) and elemental phosphorus can be used without any particular limitation as long as they are industrially manufactured and sold.
[0017] Examples of the raw material containing a halogen (X) include a compound represented by the formula (M l -X m It is preferable to use at least one of a halogen compound and an elemental halogen represented by the formula (1). In the formula, M represents sodium (Na), lithium (Li), boron (B), aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), germanium (Ge), arsenic (As), selenium (Se), tin (Sn), antimony (Sb), tellurium (Te), lead (Pb), bismuth (Bi), or any of these elements bonded with oxygen or sulfur, with Li or P being preferred, and Li being more preferred. X is a halogen element selected from F, Cl, Br and I. Furthermore, l is an integer of 1 or 2, and m is an integer of 1 to 10. When m is an integer of 2 to 10, that is, when there are multiple Xs, Xs may be the same or different. For example, in SiBrCl3 described later, m is 4, and Xs are composed of different elements, Br and Cl.
[0018] Specific examples of halogen compounds include sodium halides such as NaI, NaF, NaCl, and NaBr; lithium halides such as LiF, LiCl, LiBr, and LiI; boron halides such as BCl3, BBr3, and BI3; aluminum halides such as AlF3, AlBr3, AlI3, and AlCl3; silicon halides such as SiF4, SiCl4, SiCl3, Si2Cl6, SiBr4, SiBrCl3, SiBr2Cl2, and SiI4; phosphorus halides such as PF3, PF5, PCl3, PCl5, POCl3, PBr3, POBr3, PI3, P2Cl4, and P2I4; SF2, SF4, SF6, and S2F 10 , SCl2, S2Cl2, S2Br2, etc.; germanium halides such as GeF4, GeCl4, GeBr4, GeI4, GeF2, GeCl2, GeBr2, GeI2, etc.; arsenic halides such as AsF3, AsCl3, AsBr3, AsI3, AsF5, etc.; selenium halides such as SeF4, SeF6, SeCl2, SeCl4, Se2Br2, SeBr4, etc.; tin halides such as SnF4, SnCl4, SnBr4, SnI4, SnF2, SnCl2, SnBr2, SnI2, etc.; antimony halides such as SbF3, SbCl3, SbBr3, SbI3, SbF5, SbCl5, etc.; TeF4, Te2F 10 , tellurium halides such as TeF6, TeCl2, TeCl4, TeBr2, TeBr4, TeI4, etc.; lead halides such as PbF4, PbCl4, PbF2, PbCl2, PbBr2, PbI2, etc.; bismuth halides such as BiF3, BiCl3, BiBr3, BiI3, etc.
[0019] Among these, preferred are lithium halides such as lithium chloride (LiCl), lithium bromide (LiBr), and lithium iodide (LiI), and phosphorus halides such as phosphorus pentachloride (PCl5), phosphorus trichloride (PCl3), phosphorus pentabromide (PBr5), and phosphorus tribromide (PBr3).Of these, lithium halides or PBr3 are preferred, lithium halides are more preferred from the viewpoint of ease of handling, and LiCl and LiBr are even more preferred from the viewpoint of further increasing ion conductivity. The halogen compound may be used alone or in combination of two or more of the above compounds.
[0020] In this embodiment, a compound obtained by reacting the above raw materials may be used. For example, Li3PS4 may be synthesized from Li2S and P2S5, and Li3PS4, Li2O, and LiX may be used as raw materials. Li3PS4 may be crystalline or amorphous, or may be a mixture of crystalline and amorphous.
[0021] In one embodiment, it is preferable to use at least one of Li2O and LiOH as the raw material. Furthermore, it is preferable to use Li2S, Li2O, P2S5, and LiX (X is a halogen) as the raw material. For example, when Li2S, Li2O, P2S5, and LiX are used as the raw materials, the molar ratio of the input raw materials can be Li2S:Li2O:P2S5:LiX=1.5-1.9:0.01-0.8:0.5:1.0-2.0.
[0022] In the mixing step, the above-mentioned raw materials are mixed. The mixing method is not particularly limited, and any known method can be used. In this embodiment, the raw materials may be subjected to mechanical stress to react while being mixed, or may be pulverized while being mixed. Here, "applying mechanical stress" means mechanically applying shear force, impact force, or the like. Examples of means for applying mechanical stress include pulverizers such as planetary ball mills, vibration mills, rolling mills, and bead mills, and kneaders such as single-shaft kneaders and multi-shaft kneaders. The mixing step may be carried out in the presence of a solvent (wet mixing) or without the use of a solvent (dry mixing).
[0023] In the case of dry mixing, the conditions for pulverization and mixing may be, for example, when a planetary ball mill is used as a pulverizer, a rotation speed of several tens to several hundreds of revolutions per minute and processing for 0.5 to 100 hours. More specifically, in the case of the planetary ball mill (manufactured by Fritsch: model number P-7) used in the examples of the present application, the rotation speed of the planetary ball mill is preferably 350 rpm or more and 400 rpm or less, more preferably 360 rpm or more and 380 rpm or less. When balls serving as grinding media are used, for example, zirconia balls, their diameter is preferably 0.2 to 20 mm.
[0024] In one embodiment, wet mixing is preferred as it may suppress the formation of β-Li3PS4. As the solvent, an organic solvent can be used, and preferably a non-polar solvent, a polar solvent, or a mixture thereof can be used. A non-polar solvent or a solvent mainly composed of a non-polar solvent, for example, 95% by mass or more of the total organic solvent is preferably a non-polar solvent.
[0025] The non-polar solvent is preferably a hydrocarbon solvent, and the hydrocarbon solvent may be a saturated hydrocarbon, an unsaturated hydrocarbon, or an aromatic hydrocarbon. Examples of saturated hydrocarbons include hexane, pentane, 2-ethylhexane, heptane, decane, tridecane, and cyclohexane. Examples of unsaturated hydrocarbons include hexene, heptene, and cyclohexene. Examples of aromatic hydrocarbons include toluene, xylene, ethylbenzene, decalin, and 1,2,3,4-tetrahydronaphthalene. Of these, toluene or xylene is preferred.
[0026] The hydrocarbon solvent is preferably dehydrated in advance, specifically, the water content is preferably 100 ppm by mass or less, and more preferably 30 ppm by mass or less.
[0027] In one embodiment, the organic solvent preferably contains at least one of a nitrile compound and an ether compound. Examples of the ether compounds include tetrahydrofuran and diethyl ether. Nitrile compounds include R(CN) n In the formula, R is an alkyl group having 1 to 10 carbon atoms, or a group having an aromatic ring having 6 to 18 ring carbon atoms. n is 1 or 2.
[0028] Examples of the nitrile include acetonitrile, propionitrile, 3-chloropropionitrile, benzonitrile, 4-fluorobenzonitrile, tertiary butyronitrile, isobutyronitrile, cyclohexylnitrile, capronitrile, isocapronitrile, malononitrile, and fumaronitrile. Preferred are propionitrile, isocapronitrile, and isobutyronitrile. For example, nitrile compounds are preferred because they form an azeotrope with toluene and are therefore easily removed from the treated product together with toluene during drying. The amount of the nitrile compound and the ether compound contained in the organic solvent is preferably from 0.01 to 5% by mass, more preferably from 0.1 to 3% by mass, and particularly preferably from 0.3 to 1% by mass.
[0029] It is preferable to use a bead mill for wet mixing. By mixing and grinding with a bead mill, the grain size of each raw material can be made smaller, which shortens the diffusion path of each element during the heating process and makes it easier for each element to be used to generate the argyrodite-type crystal structure, which is thought to suppress the generation of heterophases such as the Li3PS4 crystal structure.
[0030] The mixture of raw materials obtained by removing the solvent from the processed material after wet mixing using a bead mill is mainly composed of fine crystals. By mixing and grinding the raw materials, the raw materials are atomized, and a mixture of fine crystals of each raw material is obtained.
[0031] The mixture of raw materials may be calcined. In one embodiment, the mixture of raw materials is obtained by removing the solvent as described above, and then calcined to obtain a powdered calcined product. The heating temperature and time in the calcination can be appropriately adjusted in consideration of the composition of the calcined product, etc. For example, the heating temperature is preferably 150°C to 300°C, more preferably 160°C to 280°C, and particularly preferably 170°C to 250°C. The heating time is preferably 0.1 to 8 hours, more preferably 0.2 to 6 hours, and particularly preferably 0.25 to 4 hours.
[0032] The heating device used in the calcination is not particularly limited. For example, a shear type dryer such as an FM mixer or a Nauta mixer, a stationary furnace such as a hearth kiln, or a rotary furnace such as a rotary kiln may be used. Drying may be performed before the calcination, or drying and calcination may be performed simultaneously. The atmosphere for the calcination is not particularly limited, but an inert gas atmosphere such as nitrogen or argon is preferable.
[0033] When the mixture of raw materials is calcined in a solvent, the above-mentioned non-polar solvent, polar solvent, or a mixture thereof can be used as the solvent used for calcination. The mixture is dispersed in the solvent to form a slurry, which is then heated. The solvent used for calcination may be the same as or different from the solvent used for mixing the raw materials. When the same solvent is used, this is preferred because it does not require a step of removing the solvent.
[0034] The heating temperature and time in the calcination can be appropriately adjusted in consideration of the composition of the raw materials. For example, the heating temperature is preferably 150°C to 300°C, more preferably 160°C to 280°C, further preferably 170°C to 270°C, and particularly preferably 180°C to 260°C. By setting the temperature within the above range, the PS4 structure is formed, and halogen is easily incorporated into the argyrodite-type crystal structure. Since the raw material mixture of fine crystals is calcined in a solution, it is possible to form crystals containing the PS4 structure at a relatively low temperature. The heating time is preferably from 10 minutes to 6 hours, more preferably from 10 minutes to 3 hours, and particularly preferably from 30 minutes to 2 hours. There are no particular limitations on the heating device used in the calcination, but when the heating temperature exceeds the boiling point of the solvent used, it is preferable to use an autoclave.
[0035] The solvent is removed from the slurry used in the calcination to recover the calcined product. The method for removing the solvent is not particularly limited, but the solvent can be distilled off under normal pressure or reduced pressure. In order to further increase productivity, filtration can also be used in combination.
[0036] In the heating step, the mixture or the calcined product obtained in the mixing step is heated to obtain a solid electrolyte. The heating temperature and time can be appropriately adjusted in consideration of the composition of the mixture and the calcined product. For example, the heating temperature is preferably 300°C to 470°C, more preferably more than 300°C to 460°C or less, more preferably 320°C to 450°C, further preferably 350°C to 440°C, and particularly preferably 380°C to 430°C. The heating time is preferably from 1 to 360 minutes, more preferably from 5 to 120 minutes, and particularly preferably from 10 to 60 minutes. The atmosphere during heating is not particularly limited, but is preferably not a hydrogen sulfide gas flow but an inert gas atmosphere such as nitrogen, argon, etc. For the heating step, a firing furnace such as a stationary hearth kiln or a rotary kiln can be used. When the calcined product is heated, the above-mentioned non-polar solvent, polar solvent, or a mixture thereof can be used as the solvent used for heating. Heating is performed on the slurry in which the calcined product is dispersed in the solvent. The solvent used for heating may be the same as or different from the solvent used in the calcination. When the same solvent is used, it is preferable because a process of replacing or removing the solvent before heating is not required. Also, as with the calcination, when the heating temperature exceeds the boiling point of the solvent used, it is preferable to use an autoclave.
[0037] The solid electrolyte obtained by the production method of the present embodiment can be confirmed to have an argyrodite-type crystal structure by powder X-ray diffraction measurement using CuKα radiation, which shows diffraction peaks at 2θ=25.2±0.5 deg and 29.7±0.5 deg. The diffraction peaks at 2θ=25.2±0.5 deg and 29.7±0.5 deg are peaks derived from an argyrodite-type crystal structure. The diffraction peaks of the argyrodite crystal structure may also appear at 2θ=15.3±0.5 deg, 17.7±0.5 deg, 31.1±0.5 deg, 44.9±0.5 deg, and 47.7±0.5 deg, for example. The solid electrolyte may have these peaks.
[0038] In this application, the position of the diffraction peak is judged as A±0.5 deg or A±0.4 deg when the median is A, but A±0.3 deg is preferable. For example, in the case of the diffraction peak at 2θ=25.2±0.5 deg described above, the median A is 25.2 deg, and it is preferable that the position is in the range of 2θ=25.2±0.3 deg. The same applies to the judgment of all other diffraction peak positions in this application.
[0039] The solid electrolyte may contain a part of an amorphous component as long as it has an X-ray diffraction pattern of the argyrodite crystal structure as described above. The amorphous component shows a halo pattern in which the X-ray diffraction pattern does not substantially show peaks other than those derived from the raw material in X-ray diffraction measurement. The amorphous component may also contain a crystal structure or raw material other than the argyrodite crystal structure.
[0040] [Second embodiment] The solid electrolyte according to this embodiment has an argyrodite-type crystal structure containing lithium (Li), phosphorus (P), sulfur (S), oxygen (O) and halogen (X) as constituent elements, the proportion of Li3PO4 crystal structures in the total crystals in the solid electrolyte is 0.1 mass% or more and 3.0 mass% or less, and satisfies the following formulas (21) to (23). 4.8≦Li / P≦5.3 (21) 3.8≦S / P≦4.4 (22) 1.0 <X / P≦2.0 ···(23) (Equation (21) is the molar ratio of Li to P, equation (22) is the molar ratio of S to P, and equation (23) is the molar ratio of halogen (X) to P.)
[0041] It is preferable that the above formulas (21) to (23) satisfy the following formula: 4.85≦Li / P≦5.25 3.9≦S / P≦4.3 1.2≦X / P≦1.9 More preferably, the above formulas (21) to (23) satisfy the following formula: 4.9≦Li / P≦5.2 4.0≦S / P≦4.2 1.4≦X / P≦1.8
[0042] The proportion of the Li3PO4 crystal structure in the total crystals in the solid electrolyte is 0.1% by mass to 3.0% by mass, which makes it possible to suppress the generation of hydrogen sulfide while maintaining high ionic conductivity. The proportion of the Li3PO4 crystal structure is preferably 0.3 mass% or more, more preferably 0.5 mass% or more, and more preferably 2.0 mass% or less, more preferably 1.5 mass% or less, and more preferably 1.0 mass% or less.
[0043] In one embodiment, the proportion of the argyrodite crystal structure in the total crystals in the solid electrolyte is 90 mass % or more, which makes it possible to achieve high ionic conductivity. The proportion of the argyrodite crystal structure is preferably 93% by mass or more, more preferably 95% by mass or more, even more preferably 96% by mass or more, and particularly preferably 97% by mass or more.
[0044] In one embodiment, the proportion of the β-Li3PS4 crystal structure in the total crystals in the solid electrolyte is 5.0 mass % or less, preferably 4.0 mass % or less, and more preferably 3.0 mass % or less.
[0045] The proportions of the argyrodite-type crystal structure, the Li3PO4 crystal structure, and the β-Li3PS4 crystal structure in the total crystals in the solid electrolyte are values determined by synchrotron radiation analysis as in the evaluation example.
[0046] The compositions of the formulas (21) to (23) of this embodiment can be realized by adjusting the blending amount of the raw materials. For example, the molar ratio of S can be lowered by reducing the blending amount of lithium sulfide (Li2S), and the molar ratios of Li and O can be adjusted by blending lithium oxide (Li2O). The solid electrolyte according to this embodiment can be obtained, for example, by the manufacturing method according to the first embodiment described above.
[0047] In the solid electrolyte of the present embodiment, examples of the halogen (X) include F, Cl, Br, and I. The type of halogen (X) contained in the solid electrolyte may be one type or two or more types, but is more preferably two types. It is preferable that at least one of X is Cl or Br, and further, it is preferable that X contains Cl and Br.
[0048] In the solid electrolyte of one embodiment, in addition to the above Li, P, S, O and halogen (X), one or more elements selected from the group consisting of H, Si, Ge, Sn, Pb, B, Al, Ga, As, Sb and Bi can be contained to such an extent that the effects of the invention are not impaired.
[0049] In one embodiment, the solid electrolyte has a composition represented by the following formula (A). Li a P b S c O d X e ···(A) (In the formula, X is a halogen, a to e represent the composition ratios of the respective elements, and 4.8 ≦ a ≦ 5.3, b = 1, 3.8 ≦ c ≦ 4.4, 0 < d ≦ 0.8, 1 < e ≦ 2.0 are satisfied.)
[0050] X in formula (A) may be one selected from the group consisting of F, Cl, Br and I, or may be two or more (x1, ···, x n :n is an integer of 2 or more and 4 or less). It is more preferable that X consists of two kinds (x1, x2). The molar ratio of each element is not particularly limited. X in formula (A) is preferably Cl and Br.
[0051] In the present application, the molar ratio and composition of each element in the solid electrolyte can be measured by various methods known to those skilled in the art, but except for special circumstances such as difficulty in analysis, it can be measured by ICP emission spectrometry. For example, in the case of the solid electrolyte described in the present application, the molar ratio and composition of elements other than oxygen can be measured by ICP emission spectrometry. The molar ratio of each element can be controlled by adjusting the content of each element in the raw material.
[0052] In the solid electrolyte according to one embodiment, the lattice constant of the argyrodite-type crystal structure is preferably 9.820 Å or less, more preferably 9.815 Å or less, even more preferably 9.811 Å or less, and particularly preferably 9.810 Å or less, from the viewpoint of further suppressing hydrogen sulfide generation. It is presumed that a lattice constant within the above range indicates that the sulfur elements in the 4a and 4d sites in the argyrodite-type crystal structure are sufficiently reduced and replaced by halogen elements having smaller ionic radii. The lattice constant can be measured by synchrotron radiation analysis described in the Examples.
[0053] In the solid electrolyte according to one embodiment, from the viewpoint of further increasing ionic conductivity, it is preferable that the ratio of the peak intensity of the diffraction peak attributable to the Li3PS4 crystal structure to the diffraction peak at 2θ=25.2±0.5 deg attributable to the argyrodite-type crystal structure is less than 0.04. This is because the ionic conductivity of Li3PS4 is lower than that of the argyrodite-type crystal structure, and therefore the lower the content of the Li3PS4 crystal structure in the solid electrolyte, the more the decrease in ionic conductivity can be suppressed.
[0054] As already mentioned, normally, when the amount of Li2S in the raw materials for the solid electrolyte is reduced in order to suppress the generation of hydrogen sulfide, the sulfur element necessary to form the argyrodite crystal structure becomes deficient, making it easier for other crystal phases such as Li3PS4 to form. However, the inventors have succeeded in suppressing the amount of Li3PS4 produced and reducing the sulfur content of the argyrodite crystal structure itself by mixing the raw materials in a specific ratio, making it possible to achieve a higher level of both suppression of hydrogen sulfide generation and ionic conductivity.
[0055] In this regard, in the invention described in Patent Document 1, the peak intensity ratio derived from Li3PS4 increases due to the reduction in Li2S. This does not mean that the sulfur element is reduced from the argyrodite-type crystal structure itself as in one embodiment of the present invention, but rather that the reduced amount of the element is converted to another crystal structure, such as Li3PS4, rather than the argyrodite-type crystal structure.
[0056] Moreover, the sulfur content is reduced to reduce the amount of hydrogen sulfide generated, while the presence of oxygen in the heating step maintains the argyrodite crystal structure and exhibits high ionic conductivity. In Patent Document 2, Li2O is simply added after the argyrodite crystal structure is generated by heating, and oxygen is not present in the heating step to form the argyrodite crystal structure as in the first embodiment. Therefore, it is difficult to exhibit high ionic conductivity while reducing the amount of hydrogen sulfide generated, as in the first embodiment.
[0057] The solid electrolyte of the present invention can be used in lithium ion batteries, etc. Specifically, it can be used in the solid electrolyte layer, positive electrode, negative electrode, etc. of the battery. In one embodiment, the lithium ion battery electrode may contain, in addition to the solid electrolyte, a known active material, a conductive assistant, etc. Also, a binder may be added. A lithium ion battery according to one embodiment includes the solid electrolyte of the present invention. In one embodiment, the lithium ion battery is an all-solid-state battery. In one embodiment, the all-solid-state battery includes a laminate including, in this order, a positive electrode current collector, a positive electrode, an electrolyte layer, a negative electrode, and a negative electrode current collector. In the lithium ion battery, it is preferable that at least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode includes the solid electrolyte of the present invention. EXAMPLES
[0058] The present invention will now be described in more detail with reference to examples. The evaluation method is as follows.
[0059] (1) Amount of hydrogen sulfide (H2S) generated by solid electrolyte A schematic diagram of the test equipment is shown in Figure 1. The test apparatus 1 mainly comprises a flask 10 for humidifying nitrogen, a static mixer 20 for mixing humidified nitrogen and non-humidified nitrogen, a dew point meter 30 (M170 / DMT152 manufactured by VAISALA) for measuring the moisture content of the mixed nitrogen, a double reaction tube 40 in which a measurement sample is placed, a dew point meter 50 for measuring the moisture content of the nitrogen discharged from the double reaction tube 40, and a hydrogen sulfide meter 60 (Model 3000RS manufactured by AMI) for measuring the hydrogen sulfide concentration contained in the discharged nitrogen, and is configured to be connected by pipes (not shown). The temperature of the flask 10 is set to 10° C. by a cooling tank 11. The tubes connecting the various components were made of Teflon (registered trademark) tubes with a diameter of 6 mm. In this diagram, the tubes are omitted, and instead the flow of nitrogen is indicated by arrows.
[0060] The evaluation procedure was as follows. About 1 g of powder sample 41 was weighed out in a nitrogen glove box with a dew point of -80°C, and placed and sealed inside reaction tube 40 so as to be sandwiched between quartz wool 42. The inside of reaction tube 40 was kept at about room temperature (25°C).
[0061] Nitrogen was supplied from a nitrogen source (not shown) at 0.02 MPa into the apparatus 1. The supplied nitrogen passed through a bifurcated branch pipe BP, and a portion of it was supplied to the flask 10 and humidified. The remainder was supplied directly to the static mixer 20 as unhumidified nitrogen. The amount of nitrogen supplied to the flask 10 was adjusted by a needle valve V.
[0062] The flow rates of non-humidified nitrogen and humidified nitrogen are adjusted with a flow meter FM equipped with a needle valve to control the dew point. Specifically, non-humidified nitrogen was supplied to the static mixer 20 at a flow rate of 800 mL / min and humidified nitrogen was supplied to the static mixer 20 at a flow rate of 10 to 30 mL / min, and mixed. The dew point of the mixed gas (a mixture of non-humidified nitrogen and humidified nitrogen) was confirmed with a dew point meter 30.
[0063] After adjusting the dew point to -30°C, the three-way cock 43 was rotated to allow the mixed gas to flow through the reaction tube 40 for 2 hours. The amount of hydrogen sulfide contained in the mixed gas that passed through the sample 41 was measured with a hydrogen sulfide meter 60, and the amount of hydrogen sulfide generated per gram of solid electrolyte (cc / g) was calculated. The amount of hydrogen sulfide was recorded at 15-second intervals. For reference, the dew point of the mixed gas after exposure was measured with a dew point meter 50. In order to remove hydrogen sulfide from the nitrogen after measurement, the nitrogen was passed through an alkali trap 70.
[0064] (2) Measurement of ionic conductivity of solid electrolytes The sample was filled into a tablet press, and a pressure of 22 MPa was applied to form a compact. Carbon was placed on both sides of the compact as electrodes, and pressure was applied again with the tablet press to produce a compact for measurement (diameter about 10 mm, thickness 0.1 to 0.2 cm). The ionic conductivity of this compact was measured by AC impedance measurement. The conductivity value was measured at 25°C.
[0065] (3) X-ray diffraction (XRD) measurement The powder of the argyrodite-type solid electrolyte produced in each example was uniformly filled into a groove with a diameter of 20 mm and a depth of 0.2 mm using glass to prepare a sample. This sample was measured using a Kapton film for XRD without exposing it to air. The 2θ position of the diffraction peak was determined by Le Bail analysis using the XRD analysis program RIETAN-FP. The powder X-ray diffraction measurement was performed using a D2 PHASER powder diffraction measurement device manufactured by BRUKER Corporation under the following conditions. The powder X-ray diffraction measurement device was installed in a room with a temperature control at 25°C. Tube voltage: 30kV Tube current: 10mA X-ray wavelength: Cu-Kα ray (1.5418Å) Optical system: Concentration method Slit configuration: Solar slit 4°, divergence slit 1mm, Uses Kβ filter (Ni plate) Detector: Semiconductor detector Measurement range: 2θ=10-60deg Step width, scan speed: 0.05deg, 0.05deg / sec In the analysis of peak positions to confirm the presence of a crystal structure from the measurement results, the XRD analysis program RIETAN-FP was used, and the baseline was corrected using the 11th-order Legendre orthogonal polynomial to determine the peak positions.
[0066] (4)ICP measurement The powder of the solid electrolyte produced in each example was weighed and collected in a vial in an argon atmosphere. An alkaline KOH solution was placed in the vial, and the sample was dissolved while taking care not to collect sulfur, and then appropriately diluted to obtain a measurement solution. This was measured using a Paschen-Runge type ICP-OES device (SPECTRO ARCOS manufactured by SPECTRO) to determine the composition. Calibration curve solutions were prepared using 1000 mg / L standard solutions for ICP measurement for Li, P, and S, and 1000 mg / L standard solutions for ion chromatography for Cl and Br. Two test solutions were prepared for each sample, and five measurements were made for each test solution, and the average value was calculated. The composition was determined by the average of the two test solutions.
[0067] Manufacturing Example 1 [Production of lithium sulfide (Li2S)] The production and purification of Li2S was carried out as follows. Toluene (Sumitomo Corporation) was used as a non-aqueous medium and was dehydrated. The moisture content was measured using a Karl Fischer moisture meter to find 100 ppm. 303.8 kg of the dehydrated mixture was added to a 500 L stainless steel reaction kettle under a nitrogen stream, followed by the addition of 33.8 kg of anhydrous lithium hydroxide (Honjo Chemical Co., Ltd.). The mixture was then maintained at 95°C while being stirred at 131 rpm with a Twin Star stirring blade. The temperature was raised to 104°C while hydrogen sulfide (Sumitomo Seika Chemicals Co., Ltd.) was blown into the slurry at a supply rate of 100 L / min. Azeotropic gas of water and toluene was continuously discharged from the reaction vessel. This azeotropic gas was dehydrated by condensing it in a condenser outside the system. During this time, toluene in an amount equal to the amount of toluene distilled was continuously supplied to keep the reaction liquid level constant. The amount of water in the condensate gradually decreased, and 24 hours after the introduction of hydrogen sulfide, no water was observed distilling out. During the reaction, the solid was dispersed in the toluene and stirred, and no water separated from the toluene. Thereafter, the hydrogen sulfide was replaced with nitrogen and flowed at 100 L / min for 1 hour. The obtained solid was filtered and dried to obtain Li2S as a white powder.
[0068] Example 1 As starting materials, Li2S, P2S5, LiBr (manufactured by Honjo Chemical Co., Ltd.), LiCl (manufactured by Honjo Chemical Co., Ltd.) and Li2O (manufactured by Fujifilm Wako Pure Chemical Co., Ltd.) of Production Example 1 were used as starting materials. The starting materials were coarsely ground by a pin mill and mixed so that the molar ratio (Li2S:P2S5:LiCl:LiBr:Li2O) of the starting materials was 1.65:0.5:1.0:0.6:0.05. Specifically, 0.402g of Li2S, 0.589g of P2S5, 0.225g of LiCl, 0.276g of LiBr, and 0.008g of Li2O were mixed. The mixture and 30 g of zirconia balls with a diameter of 10 mm were placed in a zirconia pot (45 mL) of a planetary ball mill (Fritsch: Model No. P-7) and completely sealed. The pot was filled with nitrogen. The planetary ball mill was rotated at 150 rpm and processed for 10 minutes (premixing). After that, the mixture was processed at 370 rpm for 15 hours (mechanical milling) to obtain a powder of the raw material mixture. Approximately 1.5 g of the raw material mixture was placed in a Tammann tube (PT2, manufactured by Tokyo Glass Equipment Co., Ltd.) in a glove box under an Ar atmosphere, and then placed in an electric furnace and heated. Specifically, the temperature was raised from room temperature to 380°C in 1 hour, then raised to 430°C in 30 minutes, and held at 430°C for 2 hours. The mixture was then removed from the electric furnace and allowed to cool to obtain a solid electrolyte.
[0069] Table 1 shows the molar ratio of the raw materials, the molar ratio of each element, the amount of hydrogen sulfide generated, and the ionic conductivity of the obtained solid electrolyte. The XRD pattern of the solid electrolyte is shown in Figure 2. Diffraction peaks of an argyrodite-type crystal structure were observed at 2θ = 15.6 deg, 18.1 deg, 25.6 deg, 30.1 deg, 31.5 deg, and 45.1 deg.
[0070] Examples 2 to 4, Comparative Examples 1 to 5 Solid electrolytes were produced and evaluated in the same manner as in Example 1, except that the molar ratio of the starting materials was changed as shown in Table 1. The results are shown in Table 1. XRD patterns of the solid electrolytes obtained in Examples 2 to 4 and Comparative Examples 1 to 5 are shown in Figures 3 to 10, respectively. In Example 2, diffraction peaks of an argyrodite-type crystal structure were observed at 2θ=15.6 deg, 18.1 deg, 25.6 deg, 30.1 deg, 31.5 deg, and 45.1 deg. In the solid electrolyte of Example 2, diffraction peaks derived from Li3PO4 were also observed. In Example 3, diffraction peaks of an argyrodite-type crystal structure were observed at 2θ=15.7 deg, 18.1 deg, 25.6 deg, 30.1 deg, 31.5 deg, and 45.1 deg. In Example 4, diffraction peaks of an argyrodite-type crystal structure were observed at 2θ=15.7 deg, 18.1 deg, 25.7 deg, 30.2 deg, 31.6 deg, and 45.1 deg. For Examples 2 and 4 and Comparative Examples 1, 2 and 5, the compositions of the solid electrolytes were determined by ICP measurement, and the results are shown in Table 2.
[0071] [Table 1]
[0072] [Table 2]
[0073] Example 5 The same Li2S, P2S5, LiCl, and LiBr as in Example 1, and LiOH (lithium hydroxide monohydrate manufactured by Honjo Chemical Co., Ltd., dried to form lithium hydroxide) were used as starting materials. The starting materials were coarsely ground using a pin mill and mixed so that the molar ratio (Li2S:P2S5:LiCl:LiBr:LiOH) of the starting materials was 1.6:0.5:1.0:0.6:0.2. Specifically, 0.3884g of Li2S, 0.5871g of P2S5, 0.224g of LiCl, 0.2753g of LiBr, and 0.0253g of LiOH were mixed. Thereafter, the mixture was treated in a planetary ball mill to obtain a raw material mixture, and the mixture was heat-treated to obtain a solid electrolyte, in the same manner as in Example 1. The evaluation results are shown in Table 3. The XRD pattern of the solid electrolyte is shown in Figure 11. Diffraction peaks of an argyrodite-type crystal structure were observed at 2θ = 15.6 deg, 18.0 deg, 25.6 deg, 30.1 deg, 31.5 deg, and 45.0 deg.
[0074] [Table 3]
[0075] In Table 1, in Comparative Examples 1 to 3, the molar ratio of S in the solid electrolyte is changed by the amount of Li2S added. Comparative Example 1 is one with high ionic conductivity among solid electrolytes having an argyrodite crystal structure. It is found that the ionic conductivity is excellent, but the amount of hydrogen sulfide generated is large. In Examples 1 to 4 and Comparative Examples 4 and 5, the amount of Li2S added is reduced, while Li2O is added. As a result, although the amount of S in the solid electrolyte (molar ratio of 4.1) is the same as in Comparative Example 2, Example 2 has sufficiently high ionic conductivity and the amount of hydrogen sulfide generated can be significantly suppressed. A similar tendency can be confirmed from Example 4 and Comparative Example 3. On the other hand, in Comparative Examples 4 and 5, in which Li2O was further added, the amount of hydrogen sulfide generated was large. Therefore, it was confirmed that when the S content in the solid electrolyte is reduced by reducing the amount of Li2S used, it is effective to add a predetermined amount of Li2O. Moreover, in Example 5, in which LiOH was added instead of Li2O, the same effect as in Example 2 was obtained, and it was confirmed that either raw material can be used.
[0076] Evaluation example Synchrotron radiation analysis was carried out on Examples 2 and 4 and Comparative Examples 1, 4, and 5 to analyze the lattice constant of the argyrodite-type crystal structure, and the proportions of the argyrodite-type crystal structure, Li3PO4 crystal structure, and β-Li3PS4 crystal structure in the total crystals in the solid electrolyte. Specifically, the measurements were carried out under the following conditions. The powders of the solid electrolytes produced in Examples 2 and 4 and Comparative Examples 1, 4 and 5 were loaded into 0.3 mmΦ capillaries in a glove box, and the capillary tips were sealed with a curable resin to prepare samples for synchrotron radiation analysis.
[0077] The measurements were carried out under the following conditions using the powder diffraction measurement beamline "BL19B2" of SPring-8. During the measurements, nitrogen gas at 100K was sprayed onto the sample for 1 minute using a nitrogen gas spray type sample cooling device manufactured by Rigaku Corporation, and the measurements were carried out while maintaining this state. X-ray energy: 25 keV Optical system: transmission method Detector: 1D solid-state Si detector MYTHEN (12 arrays) Detector threshold: 19keV Measurement range: 2θ=4-60deg Step width: 0.005deg Exposure time: 30 seconds x 2
[0078] The measurement data was corrected to 0.005° intervals using a script dedicated to BL19B2, and the data was used for analysis. The peak position analysis to confirm the crystal structure was performed using the XRD analysis program PDXL2 (Version 2.7.3.0) manufactured by Rigaku Corporation, and was obtained by PDXL automatic profile processing. The lattice constant and abundance ratio of the crystal structure were determined by Rietveld analysis using the following function, using the XRD analysis program PDXL2 (Version 2.7.3.0) manufactured by Rigaku Corporation, and was obtained by PDXL automatic profile processing. Peak shape: Split pseudo-Voigt function Background: Beta-spline functions Peak shift: instrument function (Δ2θ=Z+Dcosθ+Tsin2θ)
[0079] In addition, the lattice constant was analyzed after correcting the value of the X-ray energy. Specifically, CeO2 was measured under the above measurement conditions, with the temperature changed to 300K and the exposure time changed to 20 seconds, and the measurement results were subjected to Rietveld analysis under the above analysis conditions, and the value of the X-ray energy was corrected so that the lattice constant was 5.41165 Å. In addition, in analyzing the peak shape, the same profile function used for the argyrodite-type crystal structure was also applied to crystals other than the argyrodite-type crystal structure. In addition, in the Rietveld analysis, the Rwp value of 10% or less was used as a guideline for the validity of the results. The results are shown in Table 4.
[0080] [Table 4]
[0081] From Table 4, it can be seen that the lattice constants of Examples 2 and 4 are smaller than those of the Comparative Example. This is because sulfur ions (S 2- ) is missing, and instead, halogen ions with a small ionic radius occupy one or more of the 4a or 4d sites, which is presumably why the lattice constant is smaller.
[0082] Although some embodiments and / or examples of the present invention have been described in detail above, those skilled in the art can easily make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and advantages of the present invention, and therefore many such modifications are within the scope of the present invention. The contents of all documents cited in this specification and of the application from which this application claims priority under the Paris Convention are incorporated by reference in their entirety.
Claims
1. A solid electrolyte having a composition represented by the following formula (A), and having diffraction peaks at 2θ=25.2±0.5 deg and 29.7±0.5 deg in powder X-ray diffraction measurement using CuKα radiation: Li a P b S c O d X e ・・・(A) (In the formula, X is a halogen, and a to e represent the composition ratios of each element, satisfying 4.8≦a≦5.3, b=1, 3.8≦c≦4.4, 0<d≦0.8, and 1<e≦2.0.)
2. 2. The solid electrolyte according to claim 1, having an argyrodite-type crystal structure.
3. The solid electrolyte according to claim 1 or 2, wherein d satisfies 0.05≦d≦0.
8.
4. 4. The solid electrolyte according to claim 2, wherein the proportion of the argyrodite-type crystal structure in all crystals in the solid electrolyte is 90 mass % or more.
5. Li 3 P.O. 4 The solid electrolyte according to any one of claims 1 to 4, comprising a crystalline structure.
6. The amount of β-Li in the total crystals in the solid electrolyte 3 P.S. 4 The solid electrolyte according to any one of claims 1 to 5, wherein the proportion of the crystal structure is 5.0 mass% or less.
7. The solid electrolyte according to any one of claims 1 to 6, wherein the halogen (X) is at least one selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I).
8. The solid electrolyte according to any one of claims 1 to 6, wherein the halogen (X) is at least one selected from chlorine (Cl) and bromine (Br).
9. The solid electrolyte according to any one of claims 2 to 8, wherein the lattice constant of the argyrodite-type crystal structure is 9.820 Å or less.
Citation Information
Patent Citations
All-solid battery
JP2017120728A
Manufacturing method of sulfide solid electrolyte material
JP2018206630A
Sulfide-based solid electrolyte for lithium secondary batteries
JP6293383B1
Sulfide glass and crystalline solid electrolyte production method, crystalline solid electrolyte, sulfide glass and solid-state battery
WO2016067631A1
Sulfide solid electrolyte
WO2018092366A1